2021
DOI: 10.3390/biomedicines9070845
|View full text |Cite
|
Sign up to set email alerts
|

Serum miRNA Profiling for Early PDAC Diagnosis and Prognosis: A Retrospective Study

Abstract: Background: Tumor stage predicts pancreatic cancer (PDAC) prognosis, but prolonged and short survivals have been described in patients with early-stage tumors. Circulating microRNA (miRNA) are an emerging class of suitable biomarkers for PDAC prognosis. Our aim was to identify whether serum miRNA signatures predict survival of early-stage PDAC. Methods: Serum RNA from archival 15 stage I-III PDAC patients and 4 controls was used for miRNAs expression profile (Agilent microarrays). PDAC patients with comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Across the two transitions, from normal to the tumor and then tumor to F1 models, there was a small cohort of miRNAs that were shown to be DE, namely miR4534, miR4743, miR222, miR3154, and miR6831. miR-6831-5p had been previously identified as being differentially expressed in PDAC vs. normal control serum samples, as shown by Aita et al [ 76 ]. KEGG pathway analysis showed enrichment for the pancreatic cancer term.…”
Section: Discussionmentioning
confidence: 99%
“…Across the two transitions, from normal to the tumor and then tumor to F1 models, there was a small cohort of miRNAs that were shown to be DE, namely miR4534, miR4743, miR222, miR3154, and miR6831. miR-6831-5p had been previously identified as being differentially expressed in PDAC vs. normal control serum samples, as shown by Aita et al [ 76 ]. KEGG pathway analysis showed enrichment for the pancreatic cancer term.…”
Section: Discussionmentioning
confidence: 99%
“…There were 44 studies included in this review that covered the topic of the diagnostic value of 110 single circulating miRNAs [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. In those studies, miRNA expression was evaluated with real-time quantitative polymerase chain reaction (RT-Q-PCR).…”
Section: Diagnostic Performance Of Circulating Mirnamentioning
confidence: 99%
“…Profiling miRNA expression can correlate to the stage of malignant pancreatic disease and hold potential as diagnostic and prognostic markers [75,76]. A retrospective study screening 2549 human miRNAs in patient sera showed that survival-related differentially expressed miRNAs were downregulated in patients with short-term survival compared to patients with long-term survival [77]. More specifically, the expression of hsa-miR-486-5p and hsa-miR-6126 were associated with long-term survival, and hsa-miR-3135b with shortterm survival.…”
Section: Epigenetic Biomarkers In Pdacmentioning
confidence: 99%